2015
DOI: 10.5751/es-07244-200160
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of subsistence: qualitative social-ecological modeling of indigenous aquatic hunting and gathering in tropical Australia

Abstract: ABSTRACT. Subsistence remains critical to indigenous people in settler-colonial states such as Australia, providing key foundations for indigenous identities and for wider state recognition. However, the drivers of contemporary subsistence are rarely fully articulated and analyzed in terms of likely changing conditions. Our interdisciplinary team combined past research experience gained from multiple sites with published literature to create two generalized qualitative models of the socio-cultural and environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
(100 reference statements)
1
18
0
1
Order By: Relevance
“…Despite the usefulness of qualitative models (Downing et al 2014, Barber et al 2015, Martone et al 2017, we are aware of their limitations; thus, the results we have presented should be read cautiously. Our qualitative model does not include stocks and flows, and the deriving dynamic consequences from the causal loop diagram discussed could give us misleading conclusions (Vennix 1996).…”
Section: Discussion and Grounded Speculationmentioning
confidence: 99%
“…Despite the usefulness of qualitative models (Downing et al 2014, Barber et al 2015, Martone et al 2017, we are aware of their limitations; thus, the results we have presented should be read cautiously. Our qualitative model does not include stocks and flows, and the deriving dynamic consequences from the causal loop diagram discussed could give us misleading conclusions (Vennix 1996).…”
Section: Discussion and Grounded Speculationmentioning
confidence: 99%
“…Harvesting practices facilitate the intergenerational transfer of ecological and cultural knowledge, and sustain the relationships, or kinship ties between people, their spiritual beliefs and their country (Rose 1996;Seton and Bradley 2004;Toussaint 2014;Barber et al 2015). The practice reinforces social norms and the institutions governing both access to and replenishment of resources (thus the close relationships between natural, human and social capitals).…”
Section: Context For Livelihood Resourcing To Supporting Customary Hamentioning
confidence: 96%
“…Before we didn't have, used to This is particularly important when many of the older respondents shared concerns regarding the challenges in teaching some of the younger generation. Barber et al (2015) modelled the negative feedback effect on harvesting motivation of community dysfunction arising from substance dependencies.…”
Section: Context For Livelihood Resourcing To Supporting Customary Hamentioning
confidence: 99%
“…On the other hand, during a case study in Nepal, which included two workshops and a prolonged series of meetings, was realised that local communities easily lost their interest in participation over time. Qualitative social-ecological modelling was also applied to manage Indigenous aquatic hunting and gathering in tropical Australia (Barber et al, 2015). Two models including a short-term model (drivers of effort by active individuals) and a long-term model (persistence of subsistence at the community scale) were developed to predict how the systems might respond to potential perturbation.…”
Section: Local Users and Residents Or Indigenous Communities: Local Amentioning
confidence: 99%
“…shown that social-ecological systems models have been supported to be an effective means in communication among societal actors (Delgado et al, 2009, Salerno et al, 2010, Franzén et al, 2011, Barber et al, 2015. The stakeholders played a critical role in participating in the modelling process.…”
Section: Local Users and Residents Or Indigenous Communities: Local Amentioning
confidence: 99%